THE ROLE OF THE TEACHER IN SHAPEING STUDENT LEARNING BEHAVIOR IN ARABIC LEARNING - Uswatun Hidayah (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2020)
Abstract: this study aims to describe the teacher's role in shaping good student learning behavior in learning Arabic (behavioristic learning theory perspective) and the factors that influence it. This research was conducted at Madrasah Aliyah Negeri 1 Muaro Jambi in June and July 2020. The research data was obtained by interviewing the Arabic language teacher, the head of MAN 1 Muaro Jambi and the head of class XI (as the main data), as well as observing (as the main data). supporting data). The results showed that teachers at MAN 1 Muaro Jambi had carried out their roles well sincerely and patiently. The role of professional teachers had also been seen in MAN 1 Muaro Jambi because teachers were not only educators but also mentors, managers, as evaluators and the role of teachers as well. as a good role model (uswahhasanah) for students. In shaping student learning behavior, professional teachers use several ways, namely by reprimand, routine activities, with good habits and the learning taught by the teacher contains character values ​​(how to behave) in it. With several ways to shape these characters, the values ​​that have been seen in MAN 1 Muaro Jambi are religious values, honesty, discipline, curiosity and social care. In the formation of student character/behavior, there are also factors that influence it, both from internal factors, namely habits and external factors, namely environment. These factors become obstacles or supports for teachers in shaping good learning behavior for students. From the results of this study, it is suggested that teachers should increase their teaching through the teacher's own behavior directly rather than just a theory which will be a little more difficult for students to apply. Because when students see what the teacher is doing, they tend to like it more for them to do too. The point is that when the teacher gives an example of a good attitude, the students will also do the same and this is very good for shaping student learning behavior.